A MODEL OF EARTH'S DEEP INTERIOR BASEDON MINERALOGICAL DATA - Saxena S.K.; Lazor P.; Dubrovinsky L.S. (My University, 2000)
We describe here a model of formation of the core and the early history of Earth based on recent experimental mineralogical data. In a nebular setting, where differentiated planetesimals with their iron cores were plentiful, hot condensing solids mixed with the planetesimal irons and formed the solid proto-core (Fe-Ni-S-C). FeO from unmixing in magnesiowustite and from a dissociation of perovskite in the newly accreted mantle concentrated at the core-mantle interface and reacted with the nascent core. The interface grew to form the liquid core (Fe-Ni-O-S-C) at the expense of the solid proto-core and the formation of much of the outer core was complete within the first 500 million years. The model is consistent with geochemical data and has important implications for the dynamics of the inner core.